Parainfluenza Virus 5 Priming Followed by SIV/HIV Virus-Like-Particle Boosting Induces Potent and Durable Immune Responses in Nonhuman Primates - Xiao, Peng; Dienger-Stambaugh, Krista; Chen, Xuemin; Wei, Huiling; Phan, Shannon; Beavis, Ashley C.; Singh, Karnail; Adhikary, Nihar R. Deb; Tiwari, Pooja; Villinger, Francois; He, Biao; Spearman, Paul (Frontiers in Immunology, 2021)
The search for a preventive vaccine against HIV infection remains an ongoing challenge, indicating the need for novel approaches. Parainfluenza virus 5 (PIV5) is a paramyxovirus replicating in the upper airways that is not associated with any animal or human pathology. In animal models, PIV5-vectored vaccines have shown protection against influenza, RSV, and other human pathogens. Here, we generated PIV5 vaccines expressing HIV envelope (Env) and SIV Gag and administered them intranasally to macaques, followed by boosting with virus-like particles (VLPs) containing trimeric HIV Env. Moreover, we compared the immune responses generated by PIV5-SHIV prime/VLPs boost regimen in naïve vs a control group in which pre-existing immunity to the PIV5 vector was established. We demonstrate for the first time that intranasal administration of PIV5-based HIV vaccines is safe, well-tolerated and immunogenic, and that boosting with adjuvanted trimeric Env VLPs enhances humoral and cellular immune responses. The PIV5 prime/VLP boost regimen induced robust and durable systemic and mucosal Env-specific antibody titers with functional activities including ADCC and neutralization. This regimen also induced highly polyfunctional antigen-specific T cell responses. Importantly, we show that diminished responses due to PIV5 pre-existing immunity can be overcome in part with VLP protein boosts. Overall, these results establish that PIV5-based HIV vaccine candidates are promising and warrant further investigation including moving on to primate challenge studies.